2020
DOI: 10.1080/09669582.2020.1797756
|View full text |Cite
|
Sign up to set email alerts
|

‘You feel you’re not alone’: how multicultural festivals foster social sustainability through multiple psychological sense of community

Abstract: Recognizing the limited research on social aspects of sustainability in event studies, this paper seeks to understand how multicultural festivals promote and deliver social sustainability through the facilitation of multiple psychological sense of community for attendees. By considering refugees and ethnic minority immigrants, it also addresses the gap at the nexus of events and marginalization for under-researched groups in critical event studies. Focusing on the New Beginnings Festival, an arts and culture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 60 publications
(123 reference statements)
1
26
0
Order By: Relevance
“…While some of the elements of our framework (e.g. providing a platform, giving ownership, making voices heard) have previously been explored in an events context (Arcodia and Whitford, 2007;Hassanli et al, 2019Hassanli et al, , 2020Stadler, 2013;Vorobjovas-Pinta and Hardy, 2020;Walters, 2019), studies have focused predominantly on attendees, on a single element, and not specifically on empowerment. This paper is the first to provide a holistic understanding of the process of empowerment, and to provide evidence that psychological empowerment accrues not only to event attendees from marginalised groups, but also to volunteers, stallholders and organisers.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of the elements of our framework (e.g. providing a platform, giving ownership, making voices heard) have previously been explored in an events context (Arcodia and Whitford, 2007;Hassanli et al, 2019Hassanli et al, , 2020Stadler, 2013;Vorobjovas-Pinta and Hardy, 2020;Walters, 2019), studies have focused predominantly on attendees, on a single element, and not specifically on empowerment. This paper is the first to provide a holistic understanding of the process of empowerment, and to provide evidence that psychological empowerment accrues not only to event attendees from marginalised groups, but also to volunteers, stallholders and organisers.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…To date, scholars have focused on the negative outcomes of power relationships (see for example Batty 2016;Clarke and Jepson 2011;Tiew et al, 2015) and have largely overlooked the experiences of marginalised groups. While two recent studies investigating events for ethnic minority migrants have identified the psychological benefits of such events, and noted a feeling of empowerment, they used theories of counterspace and 'psychological sense of community' respectively, rather than power dynamics (Hassanli et al, 2019(Hassanli et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Key areas of diversity also include gender, disability, generation, LGBTQIA+, Indigenous identities, and religious affiliation. Festival researchers continue to demonstrate the role such events play for our diverse communities, and their use in promoting social sustainability and equity for all (Hassanli et al, 2020). Thus, there remains a need to continue problematising and critically engaging with such ideas and practices, and facilitate the use of festivals as sites for on-going dialogue and negotiation between members of diverse communities (Finkel and Platt, 2020; Hassanli et al, 2020; Permezel and Duffy, 2007).…”
Section: Socio-cultural Impacts Of Festivalsmentioning
confidence: 99%
“…Sense of community [8,18,[30][31][32][33] A temporary and spatially restricted liminoid zone facilitates a strong sense of collectiveness with other participants (audience socialization); Shared enjoyment, collective actions and emotions Sense of belonging [30] Longer-lasting communities demonstrating a shared social identity with shared values and beliefs; for instance, refugees or ethnic minority immigrants [34], or residents of a rural countryside [35], but also communities of fans of a musician, band, musical genre, or subculture…”
Section: Dimension Characteristicsmentioning
confidence: 99%
“…Some clubs offer adolescents possibilities to do volunteering as a form of participation in the associated scene. This increases ownership, the place identity [20], and the sense of inclusion [34], but also activates adolescents in the co-production of popular culture in the long run [69].…”
Section: Sense Of Belongingmentioning
confidence: 99%